Analisis Pengaruh Kompleksitas Akuntansi Terhadap Keterlambatan Penyampaian Laporan Keuangan Interim - Syafa Alana Diningtias; Liza Alvia (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This study aims to provide empirical evidence regarding the effect of accounting complexity on delay in submitting interim financial report in consumer cyclicals sector companies listed on the Indonesia Stock Exchange for the period 2022-2024. Accounting complexity in this study is measured by the number of business segments, the number of subsidiaries and acquisitions. The population used in this study were companies that received sanctions in the form of the first warning letter in the first quarter of 2024. Approach used is a quantitative approach with logistic regression analysis as a data analysis method because this method is suitable for research that has a dependent variable with dummy variables. Determination of the research sample using purposive sampling which resulted in a sample of 153 companies. This study provides evidence that the number of business segments and acquisitions has No. influence on the delay in submitting interimfinancial reports. While the number of subsidiaries has a significant positive effect on the delay in submitting interim finansial reports.